2023
DOI: 10.3390/ani13091534
|View full text |Cite
|
Sign up to set email alerts
|

Could Insect Products Provide a Safe and Sustainable Feed Alternative for the Poultry Industry? A Comprehensive Review

Abstract: The planet is home to more than 2000 species of edible insects, some of which have been consumed as food for many years. Recently, edible insect products have been gradually increasing in several countries, such as Italy and Egypt, as novel feed resources for humans and animals due to their availability, potential economic benefits, and high nutritive value. The insect industry can provide a new solution for livestock nutrition and offer many additional advantages, but there are obstacles to overcome, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 130 publications
0
13
0
Order By: Relevance
“…Although there is still inadequate information available regarding the safety and digestibility of incorporating insect-based feeds in poultry diets, recent studies have shown that insect meals have high nutrient digestibility rates in various animal species. Therefore, insect meals have the capability to be valuable alternative ingredients in animal feed formulations [7,8]. The research findings indicate that the dietary inclusion of insects in poultry diets can enhance the growth rate and feed conversion efficiency, implying their viability as an economical and productive protein source for poultry nutrition, as indicated in Table 2.…”
Section: Digestibility Of Insect-based Feeds In Poultry Dietsmentioning
confidence: 90%
See 4 more Smart Citations
“…Although there is still inadequate information available regarding the safety and digestibility of incorporating insect-based feeds in poultry diets, recent studies have shown that insect meals have high nutrient digestibility rates in various animal species. Therefore, insect meals have the capability to be valuable alternative ingredients in animal feed formulations [7,8]. The research findings indicate that the dietary inclusion of insects in poultry diets can enhance the growth rate and feed conversion efficiency, implying their viability as an economical and productive protein source for poultry nutrition, as indicated in Table 2.…”
Section: Digestibility Of Insect-based Feeds In Poultry Dietsmentioning
confidence: 90%
“…Insects constitute a high-quality protein source, being rich in essential amino acids and lipids. Interestingly, the protein contents of insect meals can significantly vary, ranging from almost 40% to 60%, even if being derived from the same insect species [7,8,47,49]. The variance in nutrient contents can also be influenced by factors such as dietary habits, including the specific types of food they consume in their ecological niche (preferably natural feeding patterns, and how these aspects affect the nutrient content and overall nutritional profiles of insects), developmental stage, and prevailing environmental conditions, thereby leading to dissimilar nutritional profiles even amongst closely related insect taxa [50].…”
Section: Insect Meal As a Sustainable Nutrient Source In Poultry Dietsmentioning
confidence: 99%
See 3 more Smart Citations